Development of Exe Learning Based E-Module with Whatsapp Application for Online History Learning to Increase Learning Result - Budi Purnomo; Ratu Rahmini; Muhammad Afrillyan Dwi Syahputra (Journal of Education Reseach and Evaluation, 2023)
Nowdays students barely understand the content presented by the teacher due to the outbreak of the coronavirus, so learning was carried out online. Several applications are used for online based-learning. Therefore to solve that problem this research aims to develop e-modules based on exe learning with the WhatsApp application for online history learning worthy of research. This research decide the feasibillity of the product being developed and the student's response to the product. The research method for developing products uses the ADDIE model. The e-module developed was assessed and based on expert assessments. E-module trials met the eligibility criteria with a percentage of 98% from material experts with a score of 49 and a score of 53 with a percentage of 88.3% from media experts, and a score of 674 (89, 86%) and 1375 (91.53%), from small and large group trials, then the media is declared suitable for use in learning history at the senior high school level. This shows that the Whatsapp application-based exe-learning media can improve learning results. The effectiveness test also shows an increase with a comparison of the control class getting 67% completeness, compared to the experimental class with a 90% completeness level. This showed that the Whatsapp application-based exe-learning media can improve learning results.